Geronimo Stilton: The Kingdom of Fantasy #5: The Volcano of Fire (HC) - Stilton, Geronimo (Kingdom of fantasy, #5, 2013)
After receiving a mysterious message summoning him to a meeting, Geronimo Stilton finds himself back in the Kingdom of Fantasy, summoned by the Elves, who want him to travel to the Great Explanatorium to find an answer to the earthquakes that are threatening the Kingdom.